Addressing the Absence of Masculine-Sensitive Research Methods Reflections from Interviewing Military Men - Curato, Nicole (Philippine Social Sciences Review; Volume 62 No.2 July-December 2010, Ed. Eric Manalastas, 2011)
The literature on masculinity studies has been a major intellectual force in the past two decades. It engaged feminist research by providing diverse accounts of men’s experiences instead of presenting men as a coherent bloc perpetuating patriarchy. In spite of the theoretical developments and richness of empirical accounts of masculinities, it is observed that these advancements have not yet been translated to a discussion on research methods. Unlike feminist research which has generated a set of gender-sensitive methods that address the patriarchal bias of social research, there is no corresponding development in masculinity studies that bring out the sensitivities of studying men. In this piece, I aim to map out the reasons for the relatively muted discussion on masculine-sensitive methods and suggest possible responses. I suggest that that the absence of masculine methods can be responded to not by developing gender-sensitive methods that capture “the male experience” but by making “theory-led” selections of existing methods and situating the quality of the data gathered to the intersection of the researcher and respondents’ positionalities. To provide empirical grounding to my methodological conjectures, I draw on my experience in conducting fieldwork inside a detention center where military men from the Armed Forces of the Philippines were held.
Keywords: masculine